Peranan Bantuan Langsung Tunai Dana Desa dalam Pemulihan Ekonomi Masyarakat pada Massa Pandemi Covid-19 di Desa Pangi - Abdul Latif; Andi Mardiana; Misrawati Kusmin; Yolanda Abdullah (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
The purpose of this research is to provide insight and knowledge about the role of the Pangi Village government in helping communities affected by the Covid 19 pandemic and knowing the distribution channels of Village Fund Cash Direct Aid (BLT-Dana Desa), as well as knowing the impact felt by the beneficiary community. The target of this activity is the people of Pangi Village, Suwawa Timur District, Bone Bolango Regency, which consists of 3 hamlets with a population of 780 people and the number of aid recipients as many as 84 families. The results of this study found that the Pangi Village government had carried out the stages in distributing aid to the community correctly and on target, even though it had not been able to meet all their needs, but the people of Pangi Village were greatly helped by the existence of BLT-Daba Desa, besides that, they were increasingly aware about the dangers of Covid-19 and knowing how to prevent it.